PROVIDING LEGAL AID TO GEN Z OF SEXUAL VIOLANCE IN MEDAN CITY IN ACCESS TO COMPLIANCE AND JUSTICE (A STUDY AT LBH MEDAN) - Afifah Salwa, Nabila; Siagian, Fahrizal S.; Rosmalinda; Hanifah Azizah; Meirani Rubianto (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2025)
Legal aid plays a crucial role in ensuring equality before the law by providing access to justice for underprivileged individuals. This study focuses on the Gen Z community’s concerns about their preparedness in handling legal issues, particularly in cases of sexual violence. Using a normative-empirical method, combining legal norms with empirical data, the research highlights the important function of Legal Aid Institutes in preventing the abuse of power and protecting clients' interests to achieve fair court decisions. LBH Medan offers structural legal aid to Gen Z in Medan city, aiming to foster structural transformation toward greater legal compliance and justice. The study recommends that the City Government support Legal Aid Institutions by providing assistance that ensures the independence and effective operation of legal aid programs, thus reinforcing access to justice and promoting fairness in the legal system.